IFLA Public Library Service Guidelines. - Koontz, Christie (IFLA Publications, 2010)
The public library is the prime community access point designed to respond to a multitude of ever-changing information needs. These guidelines are framed to provide assistance to library and information professionals in most situations. They assist to better develop effective services, relevant collections, and accessible formats within the context and requirements of the local community. In this exciting and complex information world it is important for professionals in search of knowledge, information and creative experience to succeed. This is the 2nd edition of The Public Library Service I.